Strategi Kepala Sekolah Dalam Penerapan Suvervisi Pendidikan - Iswanto (Al-Rabwah, 2020)
Supervision of educational activities is needed by teachers, for teachers who work every day at school there are no other parties who are closer and learned from in all their activities, except the Principal. The teacher is one of the determinants of the low quality of education. The framework of the implementation of the education supervision program should include all related components and affect the success of the educational supervision program. This success is viewed from component planning, implementation, and impact of the education supervision program. Principals in carrying out their duties and responsibilities as a supervisor in an effective, then the school principal has the competence of human, managerial, and. Technical. All of them are a unity that can not be separated.